The Role of Suppression and the Maintenance of Euthymia in Clinical Settings - Merlo, Emanuele Maria; Stoian, Anca Pantea; Motofei, Ion G.; Settineri, Salvatore (Frontiers in Psychology, 2021)
Background: Defence mechanisms serve as mediators referred to the subjects’ attempt to manage stressors capable of threatening their integrity. Mature defence mechanisms represent the high adaptive group, including suppression which allows the subject to distance disturbing contents from consciousness. In line with general defensive intents, suppression would preserve stable mood states, as in the case of euthymia. Clinical issues usually disturb homeorhesis, so that the study of subjects’ suppressive tendencies would suggest possible existing relations among defence mechanisms, mood states and clinical issues. The study highlighted the significant existing relations among factors such as suppression, euthymia, mood states and clinical psychological phenomena. Methods: The observation group was composed of 150 participants, 51 males (34%) and 99 females (66%), aged from 25 to 30 years old, with a mean age of 26.63 years old (SD = 1.51). The study was conducted through the use of measures related to subjects’ characteristics, euthymia, psychological flexibility and psychological well-being (Euthymia Scale), suppression (Suppression Mental Questionnaire), wellbeing (Who-5) and compassion (Proqol-5). Results: The performed analyses consisted of descriptive statistics, correlations, differences and regressions among the considered variables. Starting from the first hypothesis, SMQ factors appeared to be significantly and positively correlated with Euthymia factors, rather than Regression in the Ego service (-). In line with the previous result, significant and positive correlations emerged among SMQ and Well-being (WHO-5) variables, maintaining an inverse relation with Regression in the Ego service. Significant differences emerged between male and female groups concerning SMQ total score and rationalization, with higher male group scores. Finally, significant dependencies emerged among the selected predictors (SMQ variables) and Compassion satisfaction. Conclusion: The emerged results highlighted significant relations among the considered variables so that it was possible to highlight the common directions assumed by suppression variables, well-being and euthymia. Moreover, suppression appeared as a significant predictor with a causal role in clinical satisfaction. The results that have emerged allow us to consider defences through an empirical perspective, useful to suggest an extension to other groups, phenomena and conditions.